Nanomechanical behaviour of the monolithic framework solids: an experimental and modelling study - Tricarico, M (2023)
Metal-organic frameworks (MOFs) have established themselves as a versatile material platform for a wide variety of applications such as gas adsorption, energy conversion and storage, luminescence and chemical sensing. Over the past two decades, scientists have designed numerous MOF systems and composites that are specifically tailored for different applications, thanks to their extraordinarily large internal surface area and high tuneability. However, the integration of MOFs into real-world sensors and devices still represents a challenge. The majority of MOFs reported to date is in fact synthesised in the form of polydisperse powders, characterised by some intrinsic limitations. The aim of this thesis is to gain understanding of the mechanical behaviour of robust monolithic sol-gel MOFs, identified as a promising candidate for the transition of this class of materials from the academia to industrial deployment. The advantages and potential applications of MOF monoliths are described in Chapter 1. An overview of nanoindentation, the most used technique for the mechanical characterisation of MOFs, is provided in Chapter 2, along with a literature review of the field of MOF mechanics. Chapter 3 summarises the synthesis protocols and the material characterisation techniques utilised throughout the thesis. In Chapters 4, 5 and 6, different aspects of the mechanical response of the prototypical MOF monoliths were systematically studied by means of nanoindentation, spectroscopy, and finite element simulations. In particular, plasticity, fracture toughness and stress-strain relationships underpinning the mechanical performance of MOF monoliths are investigated, and their connections to the nanostructure and the framework architecture are established. Finally, the reported findings are critically summarised in Chapter 7, along with a personal perspective on the future development of the field.